Dose–response of spinal manipulation for cervicogenic headache: study protocol for a randomized controlled trial. Issue 1 (December 2016) - Hanson, Linda; Haas, Mitchell; Bronfort, Gert; Vavrek, Darcy; Schulz, Craig; Leininger, Brent; Evans, Roni; Takaki, Leslie; Neradilek, Moni
Abstract Background Cervicogenic headache is a prevalent and costly pain condition commonly treated by chiropractors. There is evidence to support the effectiveness for spinal manipulation, but the dose of treatment required to achieve maximal relief remains unknown. The purpose of this paper is to describe the methodology for a randomized controlled trial evaluating the dose–response of spinal manipulation for chronic cervicogenic headache in an adult population. Methods/Design This is a mixed-methods, two-site, prospective, parallel groups, observer-blind, randomized controlled trial conducted at university-affiliated research clinics in the Portland, OR and Minneapolis, MN areas. The primary outcome is patient reported headache frequency. Other outcomes include self-reported headache intensity, disability, quality of life, improvement, neck pain intensity and frequency, satisfaction, medication use, outside care, cervical motion, pain pressure thresholds, health care utilization, health care costs, and lost productivity. Qualitative interviews are also conducted to evaluate patients' expectations of treatment. Discussion With growing concerns regarding the costs and side effects of commonly used conventional treatments, greater numbers of headache sufferers are seeking other approaches to care. This is the first full-scale randomized controlled trial assessing the dose–response of spinal manipulation therapy on outcomes for cervicogenic headache. The results of this study will provide important evidence for the management of cervicogenic headache in adults. Trial registration ClinicalTrials.gov (Identifier:NCT01530321 )